2005
DOI: 10.1089/jpm.2005.8.1214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Comprehensive, Adaptable, Life- Affirming, Longitudinal (CALL) Palliative Care Project

Abstract: CALL Care is an effective interdisciplinary intervention approach to individualize care for people living with life-threatening illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 1 publication
3
20
0
Order By: Relevance
“…Other symptoms/signs in our study also had similar results to other recent studies (Elsayem et al. 2004; von Gunten 2005; London et al. 2005; Zalenski & Raspa 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other symptoms/signs in our study also had similar results to other recent studies (Elsayem et al. 2004; von Gunten 2005; London et al. 2005; Zalenski & Raspa 2006).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, fatigue is the most common symptoms among the palliative cancer patients, which has also been found in other studies (Henriksen et al 1997;Elsayem et al 2004;von Gunten 2005;Oi-Ling et al 2005). Some studies suggested that fatigue could not be improved significantly by palliative care (London et al 2005;Oi-Ling et al 2005), while others showed similar result as ours (Elsayem et al 2004). Adoption was also observed in more than 50% of all the patients and was the second common of all symptoms in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A total of 45 articles that reported the results of 42 outcome studies of social work interventions in aging were reviewed (Alexopoulos et al, 2009;Alkema, Wilber, Shannon, & Allen, 2007;Altfeld, Pavle, Rosenberg, & Shure, 2012;Bellantonio et al, 2008;Botsford & Rule, 2004;Brumley et al, 2007;Cabness, Miller, & Flowers, 2006;Chang, Jackson, Bullman, & Cobbs, 2009;Claiborne, 2006aClaiborne, , 2006bCounsell et al, 2007;Counsell, Callahan, Tu, Stump, & Arling, 2009;Dobrof et al, 2006;Ell, Unützer, et al, 2007;Ell, Vourlekis, Lee, & Xie, 2007;Engelhardt, McClive-Reed, et al, 2006;Engelhardt et al, 2009;Engelhardt, Toseland, Gao, & Banks, 2006;Enguí-danos & Jamison, 2006;Faul et al, 2009;Gallo et al, 2007;Gellis et al, 2008;Hanson, Reynolds, Henderson, & Pickard, 2005;Holland et al, 2005;Ingersoll-Dayton, Campbell, & Ha, 2009;Johnson & Stadel, 2007;London, McSkimming, Drew, Quinn, & Carney, 2005;Miller et al, 2007;Morrison et al, 2005;Mukamel et al, 2006;Newcomer, Kang, & Graham, 2006;Oslin et al, 2004;Phelan, Williams, Penninx, LoGerfo, & Leveille, 2004;Phibbs et al, 2006;Prior, Bahret, Allen, &amp...…”
Section: Total Sample Of Outcome Studiesmentioning
confidence: 99%
“…Gabapentin helps cancer-related neuropathic pain, 1 a multidrug combination for nausea is associated with few adverse effects, 2 fatigue in patients with advanced cancer is not caused by anemia, 3 hospice chaplains perform their ministry of being with patients who want physician-assisted suicide, 4 male caregivers are stoic, 5 families say they were never told, but do not want to hear the news, 6 for-profit hospice programs serve a different patient mix and manage their services differently from nonprofit hospice programs, 7 nursing home administrators do not think their residents need hospice care, 8 and palliative care programs who serve patients before they are near the end-of-life improve quality-oflife and increase referrals for hospice care. 9 Now, we have a literature citation to back up our assertions.…”
mentioning
confidence: 97%